Analysis and Simulation of PI and PID Control Systems Using Xcos Scilab - Kurniawan, Edi (Talenta Publisher, 2020)
Research has been conducted to analysis and simulation of PI and PID control systems using Xcos-Scilab. It focused on the constant value of kp, ki, and kd in the P, PI and PID control system simulation. The system output was set into a step signal so it will be analyzed with transient response method. For comparison, the PID control system with the Ziegler-Nichols tuning method was also used. It has been done in order to find out whether the Trial and error method is more appropriate to use in the in the PID control system simulation or not. The plant used is the Servo Motor Model with transfer function . The results from the analysis of the variation of simulated control system constants, the best parameters are: P (P variation): Kp = 7, PI (P Variation): Kp = 8; Ki = 2, PI (I Variation): Kp = 5; Ki = 5, PID (P Variation): Kp = 60; Ki = 5; Kd = 2, PID (I Variation): Kp = 50; Ki = 1; Kd = 5, PID (D Variation): Kp = 50; Ki = 10; Kd = 2.